THU0052 Association between Antiphospholipid Antibodies and Arterial Thrombotic Events in Patients with Rheumatoid Arthritis. (15th July 2016) - Kim, K.-J.; Baek, I.-W.; Park, Y.-J.; Park, K.-S.; Cho, C.-S.
Abstract : Background: Antiphospholipid antibodies (aPL) were reported to be found by variable range from 5 to 75% in patients with rheumatoid arthritis (RA) but their clinical significance remains undetermined. Objectives: The aim of this study is to investigate the association of the presence of aPL with thrombotic events in patients with RA. Methods: aPL profile, including lupus anticoagulant (LAC), anti-cardiolipin antibodies (aCL), and anti-β2 glycoprotein I antibodies (aβ2 GPI), was evaluated in 360 patients with RA according to the standard guideline. Clinical and radiographic data were collected retrospectively. Results: aPL were identified in 36 patients (10.0%). LAC was the most common type (n=23, 6.4%) and aCL and aβ2 GPI were detected in 5 and 12 patients (1.4 and 3.4%), respectively. Compared to aPL-negative group, aPL-positive group included more male patients (16 (44.4%) vs. 51 (15.7%), P <0.001) and had higher rate of ever-smoker (14 (38.9%) vs. 51 (15.7%), P =0.005) while there was no difference between two groups in the age, disease duration, and body mass index as well as in the rate of diabetes, hypertension, and dyslipidemia. There was also no significant difference in the positive rate of rheumatoid factor and anti-cyclic citrullinated peptide antibody, values of inflammatory indices and radiographic scores of hand x-ray between two groups. Of note, arterial thrombotic events more commonly developed in aPL-positive group than aPL-negative (5 (13.9%) vs. 7 (2.2%), P =0.004) while venous thrombosis did not differ between two groups (0 (0.0%) vs. 3 (0.9%), P =1.000). In multivariate regression analysis, the presence of aPL, old age, hypertension, and high value of baseline C-reactive protein were independently associated with arterial thrombotic events ( P <0.05). Conclusions: A proportion of RA patients was aPL-positive, and the presence of aPL was independently associated with arterial thrombosis. This result suggests that aPL might be contributable to increased risk for arterial thrombosis in patients with RA. References: Olech E, Merrill JT. The prevalence and clinical significance of antiphospholipid antibodies in rheumatoid arthritis. Curr Rheumatol Rep 2006;8:100–8. Gladd DA, Olech E. Antiphospholipid antibodies in rheumatoid arthritis: identifying the dominoes. Curr Rheumatol Rep 2009;11:43–51. Disclosure of Interest: None declared